Synbiotic Characteristics of Soy Milk Curd for the Prevention of Pathological Fluor Albus in Female Adolescents - Safitri, Rani; Alfitri, Rosyidah; Keswara, Nila Widya (Knowledge Dynamics, 2025)
Introduction: Fluor albus is one of the problems that has long been a problem for women. Leucorrhea or Flour Albus is a symptom that most women very often experience. This disorder is the second most common problem after menstrual disorders. Fermentation of milk into milk curd is carried out with the help of lactic acid bacteria, namely Lactobacillus bulgaricus and Streptococcus thermophilus, causing microflora in the intestine. Objective: To identify the relationship between consumption of soy milk containing synbiotics and a decrease in the incidence of pathological fluor albus in adolescent girls. Materials and Methods: The population in this study was all female adolescent with fluor albus, totaling 218 students. Inclusion Criteria: female Adolescent aged 14-18 years. The sampling technique in this study was purposive sampling. Results: The results of the analysis showed that there were significant changes in the characteristics of fluor albus in the control group and the intervention group (p = 0.000 <0.05). The mean value ± standard deviation of hemoglobin in the control group (9.86 ± 1.09) and the intervention group (10.80 ± 1.47) also showed a significant difference (p = 0.000 <0.05). The average characteristics of fluor albus in the intervention group were greater than the average characteristics of fluor albus in the control group. This means that the provision of milk curd in the intervention group was able to reduce pathological fluor albus. So, the provision of milk curd has been proven to have an effect on the characteristics of the respondents' fluor albus. Conclusion: This study shows that in the pure population there is a significant difference in the practice of preventing pathological fluor albus in women in the intervention group and the control group after the implementation of the provision of milk curd.